Down with the fascist theories of "population control" and mass sterilization in India! - Hindustani Ghadar Party - Organization of Indian Marxist - Leninists Abroad:::Creator::::::::::::
The pamphlet argues that India's shortage of agricultural resources population in India was not the outcome of over-population, which is only an idea created by the bourgeoisie and aristocrats to demonize the poor. The actual reason for mass poverty and hunger was unfair distribution of economic resources created by the ruling classes of India.